2010
DOI: 10.1021/ol902688n
|View full text |Cite
|
Sign up to set email alerts
|

Phosphaalkenes in π-Conjugation with Acetylenic Arenes

Abstract: Phosphaalkene inclusion at the periphery of acetylenic arenes results in decreased band gaps of the title compounds as verified by spectroscopic and electrochemical techniques. The electronic coupling between two 1-phosphahex-1-ene-3,5-diyne units is mediated by all para-substituted arenes and increases from 4b to 4d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 19 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…[ 1c , 5 ] Recently, it has been shown that the inclusion of phosphaalkenes (a σ 2 ,λ 3 -phosphorus center) into oligoacetylenes has a pronounced effect on the energies of the frontier molecular orbitals. [ 6 ] Similar effects have been described for oligomeric and polymeric π-conjugated systems in which σ 2 ,λ 3 -phosphorus centers feature in the form of phosphaalkenes or diphosphenes. [ 7 ] A specific class of phosphorus-containing π-conjugated materials are phospholes, that is, phosphorus analogues to pyrroles.…”
Section: Introductionmentioning
confidence: 62%
“…[ 1c , 5 ] Recently, it has been shown that the inclusion of phosphaalkenes (a σ 2 ,λ 3 -phosphorus center) into oligoacetylenes has a pronounced effect on the energies of the frontier molecular orbitals. [ 6 ] Similar effects have been described for oligomeric and polymeric π-conjugated systems in which σ 2 ,λ 3 -phosphorus centers feature in the form of phosphaalkenes or diphosphenes. [ 7 ] A specific class of phosphorus-containing π-conjugated materials are phospholes, that is, phosphorus analogues to pyrroles.…”
Section: Introductionmentioning
confidence: 62%
“…In the case of 7 a , b , it is possible to protodesilylate the acetylene termini, which can then be further elaborated by desirable substituents to fine‐tune the photophysical and electrochemical properties of the F9Ps . The feasibility of such a strategy was exemplified by the deprotection of phosphaalkene 7 a with K 2 CO 3 and isolation of the terminal bis‐acetylene 8 a .…”
Section: Resultsmentioning
confidence: 99%
“…These results show that these multifunctional P,S building blocks are valuable synthons for the molecular engineering of p-conjugated molecular or polymeric conjugated systems, and extend the family of organophosphorus-based materials. [26] Experimental Section X-ray crystallography studies: Single crystals suitable for X-ray crystal analysis were obtained by slow diffusion of vapors of pentane into a solution of 4 b, 6 a, or 8 b in dichloromethane. Single-crystal data collection was performed at 100 K with an APEX II Bruker-AXS (Centre de DiffractomØtrie, UniversitØ de Rennes 1, France) with Mo Ka radiation (l = 0.71073 ).…”
Section: Resultsmentioning
confidence: 99%